Analysis of Fine Glass Waste Addition as a Filler Material for Sand Substitution on the Properties of Mortar Products - Suharto Suharto; Muhammad Amin; Muhammad Al Muttaqii; Roniyus Marjunus; Nuzullia Fitri; Suhartono Suhartono (Diponegoro University, 2021)
Inorganic glass waste can replace sand in mortar production due to its SiO2 content being greater than 70%. This study aims to analyze the increase in mortal product agility due to the substitution of sand and reducing environmental pollution. The fine glass waste used is restrained on 80 and 120 mesh sieves. The fine glass waste substitution variations are 0, 10, 20, 30, 40, and 50% of the sand weight. The results show that fine glass waste could be used as a material for sand substitution because of the content of SiO2 of 73.8%. The results from XRD indicate that the phase of fine waste glass is amorphous. The mortar was printed with a 5x5x5 cm cube mold, and it was soaked for 7, 14, and 21 days. Based on the results, the compressive strength with a high value of 13.58 MPa at 20% fine glass waste substitution and 120 mesh. The density of 2.8±0.8 g/cm3, porosity 4.40±0.001%, and absorption 2.83±0,0009%. The compressive strengths, density, porosity, absorption, XRF and XRD characterization were evaluated. The results showed that the SiO2 compound in waste glass with the right composition of 20% could significantly increase the compressive strength. Phase formation of Calcite (CaCO3), Quartz (SiO2), and Portlandite (Ca(OH)2) was formed from the results of XRF characterization